Insulin In The Carotid Sinus Increases Suprahepatic And Arterial Glucose Levels - Lemus Vidal, Mónica; Cadenas Freixas, José Luis; Tejeda Chávez, Héctor R.; Mejía Chávez, Edgar U.; Martínez Sánchez, Julián E.; Montero Villegas, Sergio A.; Valle Rubio, Claudia Z.; Maturano Melgoza, José A.; Montero Cruz, Sergio A.; Roces Dorronsoro, Elena (Revista Cubana de Investigaciones Biomédicas, 2019)
Objective: Considering that insulin is a clue hormone in glucose homeostasis, the aim of this study was to analyze the effects of this hormone infused into the isolated carotid sinus (ICS), on suprahepatic and arterial glucose levels. Methods: All procedures were carried out in accordance with the United States National Institutes of Health. Ten male Wistar rats 280-300 g anesthetized with sodium pentobarbital (5 mg /100 g i.p.) after 12 h fasting were randomly divided into control and experimental groups. Saline (100µL) or insulin (15 mIU/rat in 100 μL saline) were injected into the ICS. Blood was collected from catheters inserted in the suprahepatic vein (SHV), starting in the jugular vein and into the femoral artery (FA) were placed. Glucose levels were determined at -10 and -5 min before saline or insulin were injected in the ICS; and 1, 5, 10, 20, and 40 min after the above injection. Results:Insulin injection significantly increased glucose levels in the SHV from 128.8 ± 5.2 mg/dL to 207.4 ± 10.6 mg/dL (p = 0.00005), while in the FA they increase from 123.4 ± 6.7 mg/dL to 199.8 ± 9.6 mg/dL(p = 0.0008) at 40 min after insulin injection. Control group with saline did not show significant changes (p = 0.97 in FA) and (p = 0.34 in SHV). The comparison between both groups was significant on arterial (p = 0.007) and venous (p = 0.003) blood glucose levels. Conclusion: As other studies report overactivation of the carotid bodies and sympathetic activity increase after insulin injections in the carotid artery, we assume that insulin in the carotid bodies (CBs)) activates hepatic glycogenolysis to increase blood glucose levels (hyperglycemia).